O jockey negro Antônio Chrispim: modernidade e exclusão – uma integração híbrida em Recife (1888-1889) - Rosa, Thiago Lindemaier da (2024)
Between 1888 and 1889, the black jockey Antônio Chrispim de Oliveira was considered one of the main "stars" of Pernambuco racing. Chrispim competed in races in the three institutions that moved the urban, social and economic life of the city of Recife: Prado Pernambucano, Hipódromo do Campo Grande and Derby Club de Pernambuco. Due to the great prominence that racing provided for a number of jockeys, it was common for them to be invited to events by the agents behind racing – men linked to the political and economic elite. It was through one of these events that Antônio Chrispim met a girl of legal age, daughter of a rich and influential Portuguese merchant in the city of Recife. As the two maintained affective relationships and, as they did not have the merchant's consent, they both planned an escape to get married; however, the couple was found, and Chrispim was accused of kidnapping. Soon, the sportsman was arrested, attacked and forced to enlist in the Navy, being sent to the Fernando de Noronha penal colony. From this moment on, there were a series of demonstrations organized by the city's black population. Based on this case, I intend to analyze how the black population was integrated and disintegrated from society after the abolition of the slavery system. To this end, I have as theoretical support the works "Bourgeois Revolution in Brazil" and "Integration of Blacks in Class Society", by Florestan Fernandes. To construct the research, I used periodic sources, mainly researched in the Hemeroteca Digital Brasileira (HDB). Regarding document management, I was supported by the work of Victor Andrade de Melo, Maurício Drummond, Rafael Fortes and João Malaia Santos, entitled "Historical Research and History of Sport". Finally, I highlight that the Chrispim case allows us to understand a series of elements of Pernambuco and Brazilian society at the end of the 19th century. The present study is part of the Border, Politics and Society research line and was funded by the CAPES/DS program.